Comparison of postoperative recovery from desflurane and sevoflurane anaesthesia using laryngeal mask airway: a prospective randomized comparative study - V. Jadhav, Supriya; Gomes, Prerna; Daftary, Swati (International Journal of Research in Medical Sciences, 2018)
Background: Ambulatory surgeries necessitate safe anaesthesia and faster recovery. Sevoflurane and desflurane are proved as such effective inhalational anaesthetic agents. The aim of this study was to compare early postoperative recovery profile in patient undergoing elective ambulatory surgical operations and receiving anaesthesia with sevoflurane or desflurane using supreme LMA. Methods: This prospective study was conducted at Jaslok Hospital and Research Centre, Dr. G. Deshmukh Marg, Mumbai, from August 2014 to April 2015. Patients were randomized into two groups receiving desflurane (Group D- n=40) and sevoflurane (Group S- n=40) for maintenance of anaesthesia. Patients were monitored for recovery by using fast track criteria (FTC) score at different time intervals. Results: The demographic characteristics, hemodynamic parameters were comparable in both the groups and no statistical significance was seen among them (p>0.05). The mean time taken for postoperative recovery characteristics were significantly lower in in Group D than Group S (p=0.00). The FTC score was significantly higher in group D as compared to group S at all times (p<0.05) for thirty minutes. The prevalence of consuming additional analgesic was 12.5% in group D and 15% in group S (p=1.000). The additional antiemetic requirement was seen in 10% patients in both the groups (p=1.000).The incidence of coughing was seen in among 5% of Group D patients and in none among Group S (p=0.152). Conclusion: The study concludes that desflurane is superior to sevoflurane with respect to time of eye opening, response to verbal commands, orientation, ability to sit, early recovery profile and duration of stay in recovery room.